Optimization of operating load conditions of the synthesis branch of ammonia productions - Бабиченко, Анатолий Константинович (Technology audit and production reserves, 2013)
The problem of optimization of operating load parameters of ammonia synthesis unit was solved in the paper in the context of general problem of the need for improving the energy efficiency of domestic largecapacity units of AM1360 series. The nature of changes in basic operation parameters of the synthesis unit, in particular changes in concentration of inert gases in the cycle, was analyzed allowing to establish a reserve of reduction of variable items of energy expenditures (consumption of natural gas, water and electricity) as objective optimization function which depends on the purge gas consumption. The parametric sensitivity of load vectors of purge gas and fresh hydronitric mixture to the vector of condensing temperature was studied by the method of mathematical modeling. This allowed concluding on the possibility of minimizing the objective function under the constraints typical for industrial operating conditions by the gradientless method, using the algorithm of onedimensional seeking of function extreme in the plane of inert gases only. The indicators of energy consumption in case of deviation of inert gases concentration from the optimal level were quantitatively determined. The presented method of developing the mathematical model and optimization algorithm can be adapted to industrial environment for various series of units, taking into account the features of technological design of the systems of compression, condensation, as well as utilization of purge and tank gases.